ASSESSING KNOWLEDGE REGARDING POLYCYSTIC OVARIAN SYNDROME AMONG ADOLESCENT GIRLS - Prof. Takhellambam Kiranmala Chanu; Dr. Ravindra H.N; Vishakha Vasava; KetuPatel; Yashvi mistri; Kris Patel (The Bioscan, 2025)
Polycystic Ovarian Syndrome (PCOS) is a common endocrine disorder that significantly affects women of reproductive age, including adolescents. It presents with a wide range of symptoms such as irregular menstruation, hirsutism, acne, and obesity, and can lead to long-term complications like infertility, type 2 diabetes, and cardiovascular disorders. Despite its increasing prevalence, awareness among adolescent girls remains limited. The aim of the study is to assess the level of knowledge regarding PCOS among adolescent girls in a selected university and the examine associations between their knowledge and selected Socio-demographic variables. This study adopted a quantitative research design. In this study total 150 adolescent girls aged 12-19 years were selected using a non-probability purposive sampling technique. Data were collected using structured questionnaire that included demographic variables and knowledge-based questions related to PCOS. Descriptive and inferential statistics were used for data analysis. Findings revealed that 70% of participants had heard of PCOS; however, only 38% demonstrated excellent knowledge, 17.3% good knowledge, 13.3% average knowledge, and 31.3% poor knowledge. A statistically significant association was observed between family monthly income and knowledge levels (p = 0.026), indicating that higher income was linked with better awareness. Other variables, such as age, education, family type, and menstrual history, showed no significant association. The study concludes that although basic awareness about PCOS exists, a substantial knowledge gap remains. The findings highlight the need for structured, school-based health education programs focusing on reproductive health and PCOS awareness. Strengthening such interventions can empower adolescent girls to seek timely medical attention and adopt preventive strategies. KEYWORDS: Assess, Knowledge, Polycystic ovarian syndrome, Adolescent girls